Terreiros, marginalizações e resistências: a geografia das religiões afro-brasileiras na cidade de Santa Maria/RS - Nascimento, Taiane Flôres do (2021)
The main objective of this thesis is to understand the production of space evidences that constitute invisibility and marginalization processes as much as resistance processes of Afro-Brazilian religions in Santa Maria/RS. Considering that the Backyards are peripherical and, in a certain way, impossible to identify in the urban landscape of a city, the idea established is that residences are the backyard itself, which we call in the research “Backyard-house”. As specific objectives, we intend to: a) understand the relationship between black people marginalization in Santa Maria and the marginalization of Afro-Brazilian religions in the city; b) analyze the establishment of the Backyard space as resistance, and c) discuss about invisibility of Backyards’ materialization. As methods, ethnogeography based on interviews and fieldwork was used to understand the spaces that involve Afro-Brazilian religiosity. This research aims to insert Afro religions in the symbolic place they were dismissed, highlight their invisibility in Brazilian geographic analysis and show their importance in the construction of religious imaginary, in a space homogenized by the dominating belief. Therefore, we can consider Afro-religiosity as legitimate and has a part on the building of the social space. As results and/or impacts of the research, there is the systematization of information connected to the Religion Geography field, highlighting the Backyards as intersectional spaces and part of the religious phenomena of Santa Maria/RS.